1995
DOI: 10.1143/jjap.34.l503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Polymer Tilt Angle for Generation of Pretilt Angle in Nematic Liquid Crystal on Rubbed Polyimide Surfaces

Abstract: We have studied the effect of the polymer tilt angle for pretilt angle generation in nematic liquid crystal, 4-cyano-4′-n-penthylbiphenyl (5CB) on rubbed polyimide surfaces. The polymer tilt angle was determined by measuring induced optical retardation produced in rubbed polyimide (PI) surfaces by rubbing. We suggest that the polymer tilt angle is not related directly to the pretilt angle on rubbed PI surfaces by rubbing. We proposed a microscopic model of pretilt angle generation on rubbed PI surfaces by rubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…[7][8][9] In addition, some researchers have found that polyimides with long alkyl and fluorinated alkyl side branches generate high pretilt angles of LCs by rubbing. [11][12][13][14] Thus, they have suggested that the high pretilt angles are attributed to steric interactions between LCs and neatly aligned branched chains. That is, the long alkyl side chains oriented by rubbing are suggested to interact with LCs favorably, being involved more heavily in the alignment of LCs at the rubbed film surface than the microgrooves generated during rubbing.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In addition, some researchers have found that polyimides with long alkyl and fluorinated alkyl side branches generate high pretilt angles of LCs by rubbing. [11][12][13][14] Thus, they have suggested that the high pretilt angles are attributed to steric interactions between LCs and neatly aligned branched chains. That is, the long alkyl side chains oriented by rubbing are suggested to interact with LCs favorably, being involved more heavily in the alignment of LCs at the rubbed film surface than the microgrooves generated during rubbing.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Consequently, the ratio of rubbing strength for 0.3mm, 0.6mm and 1.2mm rubbing depth is approximately 1: 2: 4. That is to say that the rubbing strength and anchoring strength become stronger as the rubbing depth increases.…”
Section: The Effect Of Rubbing Depth On Apparent Viscositymentioning
confidence: 96%
“…The alignment mechanism on substrate surfaces is a key issue in LCD applications. The rubbing method for nematic LCs (NLCs) on PI surfaces is most widely used to achieve uniform alignment for fabricating LCDs, and the resulting LC alignment properties have been reported by many researchers [1][2][3][4][5][6][7][8][9][10][11]. The rubbing treatment has a few advantages, such as uniform alignment and a stable pretilt angle; however, the treatment introduces debris and electrostatic discharge.…”
Section: Introductionmentioning
confidence: 99%
“…LC orientation via the rubbing method uses the microgroove effect and oriented polymer chains near the film surface [1-11, 22, 23]. The pretilt angle of NLC on the PI surface may be due to the microscopic asymmetric triangles that are formed by rubbing [6]. Huang et al [25] examined the alignment characteristics of multidirectionally rubbed LC cells.…”
Section: Introductionmentioning
confidence: 99%